The Farnesyltransferase β-Subunit Ram1 Regulates Sporisorium scitamineum Mating, Pathogenicity and Cell Wall Integrity - Sun, Shuquan; Deng, Yizhen; Cai, Enping; Yan, Meixin; Li, Lingyu; Chen, Baoshan; Chang, Changqing; Jiang, Zide (Frontiers in Microbiology, 2019)
The basidiomycetous fungus Sporisorium scitamineum causes a serious sugarcane smut disease in major sugarcane growing areas. Sexual mating is essential for infection to the host; however its underlying molecular mechanism has not been fully studied. In this study, we identified a conserved farnesyltransferase (FTase) β subunit Ram1 in S. scitamineum. The ram1 mutant displayed significantly reduced mating/filamentation, thus of weak pathogenicity to the host cane. The ram1 mutant sporidia showed more tolerant towards cell wall stressor Congo red compared to that of the wild-type. Transcriptional profiling showed that Congo red treatment resulted in notable up-regulation of the core genes involving in cell wall integrity pathway in ram1 sporidia compared with that of WT, indicating that Ram1 may be involved in cell wall integrity regulation. In yeast the heterodimeric FTase is responsible for post-translational modification of Ras (small G protein) and a-factor (pheromone). We also identified and characterized two conserved Ras protein, Ras1 and Ras2 respectively, and a MAT-1 pheromone precursor Mfa1. The ras1, ras2 and mfa1 mutants all displayed reduced mating/filamentation similar as the ram1 mutant. However both ras1 and ras2 mutants were hypersensitive to Congo red while the mfa1 mutant was the same as wild-type. Overall our study displayed that RAM1 plays an essential role in S. scitamineum mating/filamentation, pathogenicity, and cell wall stability likely through signaling pathways independent of Ras and pheromone maturation.